COP26 de Glasgow: ¡Nueva utopía tecnológica y política! - Chávez-Juanito, Y.A. (2022)
From October 30 to November 13-2021, COP26 was held in Glasgow, Scotland, with the aim of reviewing the goals of the Paris Agreement-2015, the cross-cutting goals of the 2030 Agenda and proposing new commitments-in the face of urgency-for fight global warming. As a result of the important meeting, an attempt is made to carry out a critical assessment of the agreements reached at the summit under the focus of the documentary analysis of the commitments reached and their historical relationship with previous summits. The agreed key points are based on keeping the temperature rise below 1.5 °C, proposing to reduce GHG emissions by 45% by 2030 and zero emissions by 2050, doubling the financial contributions of developed countries, with the premise of eliminating fossil fuels. Faced with the potentially catastrophic climate reality that is approaching, the levels of action of the agreements were insufficient, since, to fully comply with the objective, actions must be drastically accelerated beyond the commitment, overcoming the implicit political, economic and technological interests in the cultural models of the main emitters, otherwise, there is risk of another summit with environmental hope turned into utopia.